Impacts of rotating surface and oriented magnetic field on mixed convection and melting behavior of CNT-water nanouid in a horizontal annulus - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
Combined rotational surface and inclined magnetic effects on the mixed convection and melting behavior of CNT-water nanofluid in an annulus is analyzed with finite element method. Constant temperatures are used for the inner and outer walls while the inner surface is also rotating. Melting behavior and convection features are analyzed by varying different parameters such as Hartmann number, magnetic field inclination angle, inner wall rotational speed and nanoparticle volume fraction. The average Nu value and melt fraction increase with higher values of nanoparticle solid volume fraction while reverse impact is seen for higher Ha number values. The overall heat transfer rate is reduced for higher rotational velocity of the inner wall but contribution of various hot walls to the average Nu is different. The melt front propagation can be controlled by using the rotation of the inner surface.
Keywords: Magnetic field; Melting; Finite element method; Rotation; CNT-water nanofluid